2007
DOI: 10.1016/j.physd.2007.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous coupled oscillators with hyperbolic strange attractors

Abstract: We propose several examples of smooth low-order autonomous dynamical systems which have apparently uniformly hyperbolic attractors. The general idea is based on the use of coupled self-sustained oscillators where, due to certain amplitude nonlinearities, successive epochs of damped and excited oscillations alternate. Because of additional, phase sensitive coupling terms in the equations, the transfer of excitation from one oscillator to another is accompanied by a phase transformation corresponding to some cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
8

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 14 publications
1
48
0
8
Order By: Relevance
“…The proposed principle can be implemented, for example, in systems of electronics and nonlinear optics for the generation of robust chaos. Moreover, on this principle, one can build many models manifesting various interesting phenomena of complex dynamics, like it was done with systems based on manipulation by phases of successively generated oscillatory trains (e.g., Arnold cat map dynamics [26,38], complex analytic dynamics with Mandelbrot and Julia sets [39], robust strange nonchaotic attractor [40], etc. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed principle can be implemented, for example, in systems of electronics and nonlinear optics for the generation of robust chaos. Moreover, on this principle, one can build many models manifesting various interesting phenomena of complex dynamics, like it was done with systems based on manipulation by phases of successively generated oscillatory trains (e.g., Arnold cat map dynamics [26,38], complex analytic dynamics with Mandelbrot and Julia sets [39], robust strange nonchaotic attractor [40], etc. ).…”
Section: Discussionmentioning
confidence: 99%
“…The first few examples of feasible continuous-time dynamical systems with attractors of Smale-Williams type in their Poincaré maps were suggested in a number of recent papers by Kuznetsov et al [23][24][25][26][27]. Here, the role of angular variable was played by the phase of some oscillating process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That time, such attractors were expected to be relevant for various physical situations (such as hydrodynamic turbulence), but later it became clear that the chaotic attractors, which normally occur in applications, do not relate to the class of structurally stable ones. This is an obvious contradiction to the principle of significance of the robust systems mentioned above.Recently, this inconsistency has been partially resolved by introducing a number of physically realizable systems with hyperbolic chaotic attractors [7][8][9][10]. It has been shown that simple systems of coupled oscillators that are excited alternately (in time) possess hyperbolic attractors of Smale-Williams type (for experimental realizations, see [9][10][11]).…”
mentioning
confidence: 99%
“…Recently, this inconsistency has been partially resolved by introducing a number of physically realizable systems with hyperbolic chaotic attractors [7][8][9][10]. It has been shown that simple systems of coupled oscillators that are excited alternately (in time) possess hyperbolic attractors of Smale-Williams type (for experimental realizations, see [9][10][11]).…”
mentioning
confidence: 99%